2009
DOI: 10.1158/0008-5472.can-08-4774
|View full text |Cite
|
Sign up to set email alerts
|

Targeting LMO2 with a Peptide Aptamer Establishes a Necessary Function in Overt T-Cell Neoplasia

Abstract: LMO2 is a transcription regulator involved in human T-cell leukemia, including some occurring in X-SCID gene therapy trials, and in B-cell lymphomas and prostate cancer. LMO2 functions in transcription complexes via protein-protein interactions involving two LIM domains and causes a preleukemic T-cell development blockade followed by clonal tumors. Therefore, LMO2 is necessary but not sufficient for overt neoplasias, which must undergo additional mutations before frank malignancy. An open question is the impor… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
48
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(48 citation statements)
references
References 45 publications
0
48
0
Order By: Relevance
“…It has been previously shown possible to inhibit ETS factors in whole animal models without any harm coming to normal tissue (Huang et al, 2006). As high LMO2 removal is sufficient to cause death of leukaemic cells even after acquisition of secondary genetic abnormalities (Appert et al, 2009), identification of the molecular mechanisms involved in aberrant ectopic expression of LMO2 may open up new targeted therapeutic options directed towards the impediment of upstream regulators to block the maintenance of the leukaemia phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…It has been previously shown possible to inhibit ETS factors in whole animal models without any harm coming to normal tissue (Huang et al, 2006). As high LMO2 removal is sufficient to cause death of leukaemic cells even after acquisition of secondary genetic abnormalities (Appert et al, 2009), identification of the molecular mechanisms involved in aberrant ectopic expression of LMO2 may open up new targeted therapeutic options directed towards the impediment of upstream regulators to block the maintenance of the leukaemia phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…Oncogenic addiction infers that secondary mutations are unlikely to replace the function of the initiating oncogenic event. Accordingly, it has been shown that Lmo2 function is essential for the maintenance of Lmo2-induced T-ALL in mice (36).…”
Section: Clinical-translational Advancesmentioning
confidence: 99%
“…2), and an analogous phenomenon has been reported for anti-LMO2 VL segments, which may be iDAbs that bind to zinc-binding regions of LMO2. A related effect was found with an anti-LMO2 peptide aptamer described previously that seems to interact with the zinc in LMO2 LIM finger 4 (30). IAC 3 -derived Single Domains Facilitate Recombinant Protein Production for Structural Analysis-X-ray crystallography is a key technique in facilitating the determination of the structures of many important proteins and complexes to help elucidate biological mechanisms.…”
Section: Advantages Of Iacmentioning
confidence: 80%
“…VH#576 Hinders LMO2-dependent T-cell Neoplasia-LMO2 was originally discovered because it is activated in T-cell acute leukemia by chromosomal translocations (28,29) and, using macrodrugs such as scFv and peptide aptamers, we have shown that it is required for tumor growth in transgenic mouse models of Lmo2-dependent neoplasia (11,30). We sought to further validate the anti-LMO2 VH#576 utilizing FIGURE 3.…”
Section: Iac 3 -Selected Single Domains Function In Mammalian Cells-tmentioning
confidence: 99%